Early, Computer-Aided Design/Computer-Aided Modeling Planned, Le Fort I Advancement With Internal Distractors to Treat Severe Maxillary Hypoplasia in Cleft Lip and Palate. Issue 4 (June 2017) - Chang, Catherine S.; Swanson, Jordan; Yu, Jason; Taylor, Jesse A.
Abstract : Abstract: Traditionally, maxillary hypoplasia in the setting of cleft lip and palate is treated via orthognathic surgery at skeletal maturity, which condemns these patients to abnormal facial proportions during adolescence. The authors sought to determine the safety profile of computer-aided design/computer-aided modeling (CAD/CAM) planned, Le Fort I distraction osteogenesis with internal distractors in select patients presenting at a young age with severe maxillary retrusion. The authors retrospectively reviewed our "early" Le Fort I distraction osteogenesis experience—patients performed for severe maxillary retrusion (≥12 mm underjet), after canine eruption but prior to skeletal maturity—at a single institution. Patient demographics, cleft characteristics, CAD/CAM operative plans, surgical complications, postoperative imaging, and outcomes were analyzed. Four patients were reviewed, with a median age of 12.8 years at surgery (range 8.6–16.1 years). Overall mean advancement was 17.95 + 2.9 mm (range 13.7–19.9 mm) with mean SNA improved 18.4° to 87.4 ± 5.7°. Similarly, ANB improved 17.7° to a postoperative mean of 2.4 ± 3.1°. Mean follow-up was 100.7 weeks, with 3 of 4 patients in a Class I occlusion with moderate-term follow-up; 1 of 4 will need an additional maxillary advancement due to pseudo-relapse. In conclusion, Le Fort I distraction osteogenesis with internal distractors is a safe procedure to treat severe maxillary hypoplasia after canine eruption but before skeletal maturity. Short-term follow-up demonstrates safety of the procedure and relative stability of the advancement. Pseudo-relapse is a risk of the procedure that must be discussed at length with patients and families.